DESIGN, MICROWAVE ASSISTED SYNTHESIS AND CHARACTERIZATION OF BIOLOGICALLY ACTIVE SCAFFOLDS FOR ANALGESIC AND IN-VITRO GLUCOSIDASE INHIBITORY ACTIVITY (Journal of Pharmaceutical Negative Results, 2022)
Heterocyclic compounds comprise the major family of organic compounds. These are enormously essential with wide range of synthetic, pharmaceutical and industrial applications and are famous for their biological activities. There is an extensive spectrum of biological activities shown by many compounds containing five membered heterocyclic rings in their structure. A series of some new imidazole-azetidine and indole derivatives were synthesized by using microwave assisted technique. All these compounds were characterized by means of their IR, 1H-NMR and mass spectra, TLC, physical constants and elemental analysis.Imidazole-azetidine derivatives screened for their analgesic activity by eddy’s hot plate, tail clip method, writhing method. Imidazole-azetidine have proven to be effective analgesic compounds. Indole is a bicyclic aromatic heterocyclic organic compound comprising of a six membered benzene ring fused to a five-membered nitrogen-containing pyrrole ring. A vast research has occurred on indole and its derivatives which resulted in many approved indole containing drugs in the world market as well as many are in the pipeline stages. The indole derivatives were evaluated for their in-vitro glucosidase inhibitory activity by the In-vitro glucosidase inhibitory activity assay. The acarbose use as a standard drug.The available in vitro studies have led to the recognition that the new Indole derivatives might be considered to be more effective glucosidase inhibitory activity agents.